Hydrogen bonding interaction between active methylene hydrogen atoms and an anion as a binding motif for anion recognition: experimental studies and theoretical rationalization - Agarwalla, Hridesh; Jana, Kalyanashis; Maity, Arunava; Kesharwani, Manoj K.; Ganguly, Bishwajit; Das, Amitava (Journal of Physical Chemistry A, 2014)
Two new reagents, having similar spatial arrangements for hydrogen atoms of the active methylene functionalities, were synthesized and interactions of such reagents with different anionic analytes were studied using electronic spectroscopy as well as by using 1H and 31P NMR spectroscopic methods. Experimental studies revealed that these two reagents showed preference for binding to F– and OAc–. Detailed theoretical studies along with the above-mentioned spectroscopic studies were carried out to understand the contribution of the positively charged phosphonium ion, along with methylene functionality, in achieving the observed preference of these two receptors for binding to F– and OAc–. Observed differences in the binding affinities of these two reagents toward fluoride and acetate ions also reflected the role of acidity of such methylene hydrogen atoms in controlling the efficiencies of the hydrogen bonding in anion–Hmethylene interactions. Hydrogen bonding interactions at lower concentrations of these two anionic analytes and deprotonation equilibrium at higher concentration were observed with associated electronic spectral changes as well as visually detectable change in solution color, an observation that is generally common for other strong hydrogen bond donor functionalities like urea and thiourea. DFT calculations performed with the M06/6-31+G**//M05-2X/6-31G* level of theory showed that F– binds more strongly than OAc– with the reagent molecules. The deprotonation of methylene hydrogen atom of receptors with F– ion was observed computationally. The metal complex as reagent showed even stronger binding energies with these analytes, which corroborated the experimental results.